Evaluation of Arbuscular Mycorrhizal Fungi Inoculum on Production and Nutrient Content of Pennisetum purpureum - P. D. M. H. Karti; I. Prihantoro; M. A. Setiana (Tropical Animal Science Journal, 2018)
Land for forage planting is mainly on marginal land such as acid soil. However, the constraint is the low levels of phosphorus (P) that can inhibit forage production. Arbuscula mycorrhizal fungi has been known as a biological fertilizer because the fungi can help the absorption of phosphorus (P) on the root so that can improve the forage production and quality of nutrients. This study was aimed to utilize and evaluate the use of arbuscular mycorrhizal fungi inoculum in forage production and nutritive value of Pennisetum purpureum. The experiment used a completely randomized design with two factors (2 x 4) and 4 replications. The first factor was type of AMF inoculum (A and B) and the second factor was doses of AMF (D1= 0.5 kg/planting hole, D2= 1 kg/planting hole, D3= 1.5 kg/planting hole, and D4= 2 kg/planting hole). Control treatment was carried out separately. The result showed that the highest shoot dry weight production was on AD2 and significantly different (P<0.05) from BD1 and control. There was no interaction between type and dose of inoculum on shoot dry weight production and nutrition value. The inoculum A significantly increased (P<0.05) shoot dry weight production (34.04%), crude protein content (10.21%), phosphorus uptake (40%), N content (10.53%), N uptake (38.10%), and protein production (40.15%) of P. purpureum, compared to inoculum B. It can be concluded that AMF inoculum type A was the best inoculum for forage production.